Modelling & Simulation for Friction & Wear Coefficient of Materials - et. al., Dr. Amit Kumar Gupta, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Friction and wear can be defined as the responses of a tribo-system. Coefficient of friction and wear define the state of contact of bodies not the material properties of the bodies. Although in some special cases of contact, they can be treated as the material properties of the bodies. Both friction and wear can be treated as two kinds of responses from one tribo-system and are related with each other in each and every state of contact. The friction and wear are mainly dependent on the characteristics of two sliding surfaces. The difficulty to predict and to clarify with more accuracy such phenomenon reveals the complex nature of the surfaces, which can be evaluated through material properties such as microstructure, presence of organic molecules and oxides, water vapor, geometrical irregularities and other impurities which can be absorbed from the atmosphere. The main challenge in developing software solutions in this field has been how to appropriately represent complex tribological phenomena through easy-to-use software. The expertise in tribology has shown that by replacing the constant coefficient of friction, which is commonly used in metal forming simulations, with realistic and highly accurate friction and lubrication data results in metal forming simulations of greater accuracy with enhanced simulation functionalities. The present paper introduces a computation model & Simulation for finding out the Coefficient of Friction & Wear of a material pair for different loading condition.